Myrtaceae endémicas del Perú - Kawasaki, Lucia (2006)
The Myrtaceae are represented in Peru by 20 genera and 165 species (Brako & Zarucchi, 1993; Ulloa Ulloa et al., 2004), mostly shrubs and trees. Here we recognize 39 species and one variety in ten genera as Peruvian endemics. Eugenia is the genus with the largest number of endemic species. Endemic Myrtaceae are found mainly in Humid Lowland Amazonian Forests and Mesoandean regions, between 100 and 3600 m elevation. Six endemic species have been registered to date within Peru’s protected areas system.